Pesan-pesan Dakwah dalam Serial Film Kartun UPIN dan IPIN Episode Ramadhan pada Channel Youtube Les’ Copaque Production - Saddad Ainor Richard; Hadi Ismanto (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2020)
An Islamic nuanced cartoon 'Upin dan Ipin' has a storyline that is very close to everyday life. Packed with a light and interesting story, the main character in this cartoon is an orphaned twin, they are friendly and kind. This is why the cartoon 'Upin dan Ipin' is quite interesting to study today, in the midst of many broadcasts from both TV and the internet that only present worldly pleasures. In this research the author examines how the message of da'wah in the cartoon series 'Upin dan Ipin' Espisode Ramadhan (Azam Fasting). By using Teun Van Dijk's discourse analysis structure, namely, thematic structure, schematic structure, and semantic structure. Cartoons with Islamic nuances like this are very reliable, in terms of their attractive appearance, so they can make the audience feel at home to watch. The researcher hopes that more and more cartoons like this will be presented to the public, so that they can shift shows that lack messages both on TV and the internet. From the results of this study, the researchers concluded that there is a good way to welcome the month full of blessings, namely by cleaning the surau in mutual cooperation for the benefit of praying terawih in congregation for Muslims.